Internal Factors on Effectiveness of Performance Management System S - Saepudin Eman Herman (Business and Entrepreneurial Review, 2022)
The purpose of this paper is to examine the Performance Management during Pandemic Covid 19 throughout two perspectives impulse of  standard-oriented and excellence-oriented applied it in order to improving culture organisation through real-time individual performance as well as continuous improvement organisational development through freshly insight.  A literature review is conducted using a systematic literature search design using the two perspective of performance management. The two perspectives of performance management are entirely compatible with the notion of Standard-oriented or Excellence-Oriented applied  in both contain measuring and appraising the performance workforce  addressing the productivity and quality measurement, The limitation of publication to design framework performance management, thus been impulse create the model of performance management base two perspectives